Magic Marketing dalam Etika Bisnis Global: Kajian Literatur - Mansur; Gumiandari , Septi; Hamzawi , M. Adib (Ulumuna: Jurnal Studi Keilsman, 2023)
The inability of the businessman to compete sacrifices his ethics by involving shamanism and the magical world for income and money. By presenting a shamanic spell, it can realize business development. Business skills and experience seem to be able to overcome simultaneously with the magical world. The purpose of this research is to reveal the magical meaning in marketing. Secondary data was obtained from the qualitative data of 15 selected articles after being filtered from 147 data explored using Google Scholars through the Harzing's Publish or Perish (POP) application service which was published in the last 5 years. Search using the words "magic marketing", "business spells", "mantra marketing". Then, the process of reviewing selected journals is analyzed regularly and carefully for data reduction which eliminated research topics. It was found that the words occult, magic and sleight of hand are frequently used in various world businesses. The use of the magical world in business is widespread and empirical. Even with its role it can encourage the notion of the birth of a 'new world' not only in marketing, but also in overcoming health, welfare, politics, money, love and marriage problems. The role of magicians and shamans in urban areas provides new colors in many ways and will continue to expand. So, magical meanings in music practices, lighting, health, shamanic services, politics, gamification trends, online sales, branding, virality, new worlds, and so on are efforts to expand markets and win new market shares.